2012
DOI: 10.1016/j.neuron.2012.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Sensation in a Single Neuron Pair Represses Male Behavior in Hermaphrodites

Abstract: Summary Pheromones elicit innate sex-specific mating behaviors in many species. We demonstrate that in C. elegans, male-specific sexual attraction behavior is programmed in both sexes but repressed in hermaphrodites. Repression requires a single sensory neuron pair, the ASIs. To represses attraction in adults, the ASIs must be present, active, and capable of sensing the environment during development. The ASIs release TGF-β, and ASI function can be bypassed by experimental activation of TGF-β signaling. Sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…Recent studies have indicated that this picture also holds in other organisms. For example, in Caenorhabditis elegans, male-specific sexual attraction behaviour is repressed in hermaphrodites by a single neuron pair, the ASIs, which release transforming growth factor-β during development to induce this repression 72 . Upon de-repression, hermaphrodites exhibit male behaviour using the same neuronal circuits as those used by males 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that this picture also holds in other organisms. For example, in Caenorhabditis elegans, male-specific sexual attraction behaviour is repressed in hermaphrodites by a single neuron pair, the ASIs, which release transforming growth factor-β during development to induce this repression 72 . Upon de-repression, hermaphrodites exhibit male behaviour using the same neuronal circuits as those used by males 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Hermaphrodites, in contrast, have eight sex-specific neurons, all of which regulate egg laying (reviewed in Schafer, 2005). Furthermore, some neurons common to both sexes are functionally specialized to mediate sex-specific behaviors such as response to pheromones (Jang et al, 2012;White and Jorgensen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the neurotransmitters, such as neuropeptides, serotonin (5-HT), tyramine (TA) and octopamine (OA), have been increasingly shown to be transmitters or modulators of ASH-mediated aversive behaviours [12][13][14][15] . ASI sensory neurons are reported to mediate dauer formation 16 , enable worms to learn to avoid the smell of pathogenic bacteria after ingestion via INS-6 signalling 17 , suppress male-specific sexual attraction behaviour 18 , respond to temperature stimuli to negatively modulate thermotaxis behaviour 19 , mediate diet-restriction-induced longevity 20 , modulate satiety quiescence 21 , regulate acute CO 2 avoidance 22 , repress exploratory behaviours that comprise spontaneous reversals and omega turns 5 , and inhibit ASH-mediated aversive responses to 100% 1-octanol 23 . These studies support the hypothesis that ASIs are important polymodal sensory neurons mediating or modulating worm behaviours and development.…”
mentioning
confidence: 99%